A novel cubic Zn‐citric acid‐based MOF as a highly efficient and reusable catalyst for the synthesis of pyranopyrazoles and 5‐substituted 1H‐tetrazoles. (9th April 2022) - Koolivand, Mostafa; Nikoorazm, Mohsen; Ghorbani‐Choghamarani, Arash; Mohammadi, Masoud
Abstract: A highly stable and efficient heterogeneous catalyst was successfully prepared by hydrothermal reaction of Zinc nitrate with citric acid. To produce a novel Zn‐based MOF catalyst, Zn ions were coordinated with the ligand functional groups that can be regarded as an alpha‐hydroxy acid containing three carboxylic acids (COOH) and one hydroxyl (OH) group attached to the three‐carbon skeleton. It was found that the Zn‐CA‐MOFs compound can participate as a catalyst in the synthesis of 5‐substituted 1H‐tetrazole and pyranopyrazole molecules, selectively and efficiently with high yield in a short period of time. As presented, the catalyst demonstrates excellent reusability and stability and can be recycled up to five times without significant loss of reactivity. Heterogeneity analysis showed that no leaching of active Zn species occurred during the recycling process of the heterogeneous Zn‐CA‐MOFs. Abstract : The synthesis, characterization, and catalytic activity of a novel cubic Zn‐citric acid‐based MOF have been described. A wide range of 5‐substituted 1H‐tetrazoles and pyranopyrazole molecules prepared in the moderate to high yields.